(untitled) (Research, Society and Development, 2022)
The objective of this work is to identify, through a bibliographic review, the importance of effective communication carried out by health professionals as a form of inclusion in the care of people with hearing impairment in health services, and the difficulties and obstacles that involve this practice. This is a bibliographic research, using the PICo search strategy to identify and collect the studied samples, based on the guiding question "What is the importance of effective communication carried out by health professionals as a way of inclusion in the care of people with hearing loss" in health services?”. The analysis resulted in 11 articles that were categorized and analyzed according to the profile of scientific production and the results found in evidence. The literature has shown that health professionals from different specialties, for the most part, feel unprepared to serve this public, because they do not know how to communicate through the Brazilian Sign Language. This reflects the fragility in the training of these professionals who do not have contact with LIBRAS, during graduation or after graduation, disregarding laws that guarantee the rights of deaf people.